Comparison Of Labour Productivity : A Study Of Electronic Component Assembly Plants In Malaysia And Taiwan - Te, Chew Wee (2004)
The purpose of this case study i sto identify factors that contributed to labour productivity in the semiconductor industry based on the findings from factory (M) Malaysia and factory (T), Taiwan. It has been examined that the labor productivity achievements by both factories are significantly different where factory (T) registered productivity was 53% higher as compared to factory (M).